Teachers and students’ answers to open-ended questions about distance learning: analysis of self-evaluation questionnaires in a comprehensive school in Rome - Castellana, Giusi; Rossi, Luca (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2021)
This paper presents the results of the open-ended questions of the monitoring of distance learning carried out in a comprehensive Roman school during pandemic time. The study involved the administration of three instruments: a teacher questionnaire and 2 questionnaires for students and parents. The results of the open-ended questions (distance learning strengths and weaknesses, observations) relating to teachers (138) and students (457) will be discussed in this paper. The results of close-ended questions relating to teachers, pupils and families have been presented in a previous study (Castellana & Rossi, 2021). According to the teachers, the main difficulties of the students during the period of distance learning were the lack and the inadequacy of devices and connections. The main strength was the improvement of the school curricula. On the other hand, a considerable weakness was the lack of contact with and between the pupils. According to the students, the strengths of distance learning were being able to guarantee the continuity of the school activity, both in relation to teaching and human relationships, but also an improvement of the learning environment by the use of more engaging teaching methods, a greater autonomy and flexibility in the organization of work, lessons and materials and the development of considerable IT skills. A second set of responses highlighted the difficulties which arose from the reorganisation of the school system. Among the prospects of improvement there is an intensification of the relations between teachers and pupils and the increase and regularity of video recordings.